Gamma ray shielding capability of flexible silicone rubber composites reinforced with recycled CRT glasses - Doaa A. Elsayed; Mohamed Elsafi; Esraa H. Abdel-Gawad; Shoaa M. Al-Balawi; M. I Sayyed; Ibrahim H. Saleh (Scientific Reports)
Abstract With a focus on extending the horizons of combining electronic waste (e-waste) with different materials for creating efficient, affordable, eco-friendly, and sustainable radiation shielding composites, the present study investigates the radiation shielding performance of different composites made of silicon rubber and e-waste glass. Six samples were prepared by mixing different amounts of powdered cathode ray tube (CRT) glass (0–50%) with silicon rubber (100–50%). The linear attenuation coefficients (LAC’s) of the prepared samples were experimentally measured using a high-purity germanium detector and varying energy gamma sources. Other radiation shielding parameters such as mass attenuation coefficient (MAC), transmission factor (TF), mean free path (MFP), half value layer (HVL) and radiation attenuation ratio (RAR) were calculated. The sample with the highest CRT content (SR-CRT-50) showed the highest efficiency superior to the rest of the prepared samples with maximum LAC (2.051 cm−1), maximum MAC (1.1890 cm2/g), minimum HVL (0.338 cm), and minimum TF (0.357) at the lowest energy level of 0.060 MeV. The additive of waste CRT glass to the matrix also improve the mechanical and thermal properties of composites, and accordingly the weight loss at about 620 ± 15 °C was 70.09%, 53.17%, and 32.37% for SR-CRT-0, SR-CRT-30, and SR-CRT-50, respectively. Clearly, this study demonstrated that adding waste CRT glass to the silicone rubber polymer increased its performance as a shield against ionizing photons.